Overview of Nursing Implementation on Closed Fractures to Reduce Pain Scale - Ika Rizki Cahyani; Dwi Nopriyanto (Fakultas Kedokteran, 2021)
Fractures are bone continuity damage, which can be complete, fractures can cause extreme pain, pain is a symptom that is very often found in disorders of the musculoskeletal system, pain needs to be treated appropriately according to the pain felt, so nursing action is needed in dealing with it. This research is a literature study by searching for articles through Google Scholar, to identify the description of nursing actions on closed fractures in reducing pain scale. From the results of the literature study in 3 articles, it was found that nursing actions that could be performed on closed fractures included cold compresses, deep breathing relaxation techniques, and Asmaul Husna distraction techniques.Keywords: Closed fracture, Nursing Implementation, Pain